Stress Fracture of the Hamate Hook in a Water Polo Player - Hana Ueda; Shunpei Hama; Masataka Yasuda; Kenta Minato; Masahiro Miyashita; Kishik Shin (Case Reports in Orthopedics)
Hamate hook fractures are usually caused by direct trauma while using a tennis racket or a baseball bat. We report stress fracture of the hamate hook in a water polo player without any specific trauma. We consider that the stress fracture occurred via indirect mechanisms through the flexor tendons. Strong ulnar deviation of the wrist during ball release and strong grip on a ball with outstretched fingers, which are unique to water polo, were the likely causes of the stress fracture of the hamate hook.